2019
DOI: 10.3389/fmicb.2019.01805
|View full text |Cite
|
Sign up to set email alerts
|

Fishing in the Soup – Pathogen Detection in Food Safety Using Metabarcoding and Metagenomic Sequencing

Abstract: In food safety the detection of food contaminations with pathogenic microorganisms is a race against time and often outpaced by error-prone epidemiological approaches. For evidence-based outbreak investigations fast and reliable techniques and procedures are required to identify the source of infection. Metagenomics has the potential to become a powerful tool in the field of modern food safety, since it allows the detection, identification and characterization of a broad range of pathogens in a single experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 61 publications
3
54
0
Order By: Relevance
“…Nevertheless, we found that all assemblies were overall very similar, with respect to assembly length, N50, GC and the number of CDSs, with a few notable exceptions. In particular, assemblies constructed from short read data of laboratories LC06 and LC08 (both using a MiSeq Illumina instrument) had much lower N50 values and a greater number of contigs, probably due their use of the Nextera XT DNA Library Preparation Kit, which was recently shown to have a strong GC bias (Grützke et al, 2019;Sato et al, 2019;Uelze et al, 2019) (also compare Supplementary File 7). This is a concern since a high number of contigs in a genome assembly may cause a fragmentation of genes at the contigs borders, thereby affecting gene annotation and multilocus sequence typing.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we found that all assemblies were overall very similar, with respect to assembly length, N50, GC and the number of CDSs, with a few notable exceptions. In particular, assemblies constructed from short read data of laboratories LC06 and LC08 (both using a MiSeq Illumina instrument) had much lower N50 values and a greater number of contigs, probably due their use of the Nextera XT DNA Library Preparation Kit, which was recently shown to have a strong GC bias (Grützke et al, 2019;Sato et al, 2019;Uelze et al, 2019) (also compare Supplementary File 7). This is a concern since a high number of contigs in a genome assembly may cause a fragmentation of genes at the contigs borders, thereby affecting gene annotation and multilocus sequence typing.…”
Section: Discussionmentioning
confidence: 99%
“…Each metagenomic approach provides different levels of analysis. 16S rDNA has the most sensitive detection limit, requiring the lowest initial CFU, but the lowest resolution, reporting at the genus level because some species have almost identical 16S rDNA genes and the fragment of the 16S rDNA used is relatively small (39). Shotgun metagenomic WGS provides a less sensitive detection limit (above 10 3 CFU/ml), but provides information from species to a strain level, including many functional genes in the microbiome sample analyzed (33,36,40,41).…”
Section: Introductionmentioning
confidence: 99%
“…Metagenomic analyses can be made either using short or long sequencing reads technologies. Short-read shotgun metagenomics was most commonly used for microbiome analyses (30)(31)(32)35,39,39,42), while the use of long-read metagenomics is on the rise in the last few years (36)(37)(38)40) for numerous reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, 16S rDNA amplicon and shotgun metagenomic sequencing are the two common approaches used to address different aspects of gut microbiota in various pathological conditions including inflammatory bowel disease, diabetes, and obesity [10]. In comparison with 16S rDNA amplicon sequencing, shotgun metagenomic offers greater sensitivity, specificity, microbial abundance estimation, and greater resolution of microbes up to the species level [11]. Evidence support the fact that various pathogenic microbes can be transmitted from animals to humans or from humans to animals either through direct contact or while living with livestock in close contact and it has been exemplified by a recent report indicating the transmission of antibiotic-resistant bacteria including methicillin-resistant Staphylococcus aureus (MRSA), multidrug-resistant Staphylococcus aureus, and various members of extended-spectrum beta-lactamase (ESBL) producing Enterobacteriaceae [12][13][14].…”
Section: Introductionmentioning
confidence: 99%